(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The purpose of this study was to describe the role of the Family Welfare and Empowerment Team (PKK) in reducing the number of stunting cases in Lito Village, PaguyamanPantai District, Boalemo Regency. In this study, the research approach used is a qualitative approach with descriptive research type. Data collection is carried out in natural settings (natural conditions), primary data sources and data collection techniques that are mostly involved in observation as well as in-depth interviews and documentation. The data analysis technique used is a data analysis technique by processing data using the Miles and Huberman model. The results showed that 1) the role of the Lito Village Family Welfare and Empowerment Mobilizing Team in promotive services for stunting reduction in Lito Village, PaguyamanPantai District, Boalemo Regency was running well. The role of the Lito Village Family Empowerment and Welfare Mobilizing Team in preventive services for stunting reduction in Lito Village, PaguyamanPantai District, Boalemo Regency is in accordance with the provisions laid down. there is. The only weakness lies in the lack of good cooperation in carrying out stunting prevention. And 3) The role of the Lito Village Family Welfare and Empowerment Mobilization Team in curative services for stunting reduction in Lito Village, Paguyaman Pantai District, Boalemo Regency has been running conducively, the biggest problem is the lack of budget in maximizing stunting healing for children and toddlers in Lito Village.